Development and regeneration dynamics of the Medaka notochord - Seleit, Ali; Groß, Karen; Onistschenko, Jasmin; Centanin, Lázaro (Developmental biology, 2020)
The notochord is an embryonic tissue that acts as a hydrostatic skeleton until ossification begins in vertebrates. It is composed of outer sheath cells and inner vacuolated cells, which are generated from a common pool of disc-shaped precursors. Notochord extension during early embryogenesis is driven by the growth of vacuolated cells, reflecting in turn the expansion of their inner vacuole. Here we use desmogon, a novel desmosomal cadherin, to follow notochord development and regeneration in medaka (Oryzias latipes). We trace desmogon ​+ disc-shaped precursors at the single cell level to demonstrate that they operate as unipotent progenitors, giving rise to either sheath or vacuolated cells. We reveal that once specified, vacuolated cells grow asynchronously and drive notochord expansion bi-directionally. Additionally, we uncover distinct regenerative responses in the notochord, which depend on the nature of the injury sustained. By generating a desmogon CRISPR mutant we demonstrate that this cadherin is essential for proper vacuolated cell shape and therefore correct notochord and spine morphology. Our work expands the repertoire of model systems to study dynamic aspects of the notochord in vivo, and provides new insights in its development and regeneration properties.
Gesehen am 22.07.2020